Reconstruction options in recurrent dermatofibrosarcoma protuberans:A scoping review - Vishal Mago; Arush Pasricha (Rare Tumors, 2022)
Background This review will outline the evaluation, diagnosis, and management of dermatofibrosarcoma protuberans and emphasizes multidisciplinary role of nurses, plastic surgeons and radiation oncologist in this recurrent metastatic lesion. It pinpoints affected population at risk, clinical features, and reconstruction options. No analytical research has been done in this area. Material and Methods A scoping review of patients of DFSP who underwent reconstruction after excision of tumors was performed in the Department of Burn and Plastic Surgery, AIIMS Rishikesh. It used a five framework approach. A review of 85 similar cases reported in the literature have been scrutinized in relation to the reconstruction options, sites of the tumor, margins of excision and recurrence. Results 85 full length English studies were included out of the 445 cases found in Pubmed and related search engines to reveal various reconstructive options in reconstruction of DFSP defects. Present scoping review identifies free anterolateral thigh flap to be useful in 7 review articles followed by propeller flaps in 3 isolated case reports. 2 cases of free latissimus dorsi flap were used for reconstruction of abdominal defects. Conclusion All patients should undergo a strict screening protocol where the health personnel can play a crucial role by educating parents on the follow up and report new lesions as early as possible. All operated tumor patients can be given safety tips and education on care and risks after reconstruction with skin flaps or skin grafting . A multidisciplinary approach between the surgeon, nurse and radiation oncologist is needed for effective management of these lesions.